2014
DOI: 10.1001/jamaoto.2013.6777
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Outcomes Using Intensity-Modulated Radiation Therapy and 3-Dimensional Conformal Radiation Therapy in Treatment of Oropharyngeal Cancer

Abstract: The use of IMRT significantly improves PEG tube and toxicity-related outcomes compared with 3D-CRT in the treatment of oropharyngeal primary cancers. Given the association between mucosal toxic effects, PEG tube dependence, and dysphagia, these findings may be an indication of improved swallowing outcomes with IMRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 24 publications
5
39
0
2
Order By: Relevance
“…Recent studies on IMRT have reported better treatment outcomes and far fewer complications in the treatment of patients with head and neck cancer (Kraaijenga et al, 2015; Lohia et al, 2014; Vergeer et al, 2009; Setton et al, 2012). A study by Chen et al reported an incidence of 5.7% in nasopharyngeal carcinoma patients treated by IMRT (Chen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on IMRT have reported better treatment outcomes and far fewer complications in the treatment of patients with head and neck cancer (Kraaijenga et al, 2015; Lohia et al, 2014; Vergeer et al, 2009; Setton et al, 2012). A study by Chen et al reported an incidence of 5.7% in nasopharyngeal carcinoma patients treated by IMRT (Chen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The advent of IMRT allows dose distribution that is more conformal to tumor, involved neck, and high-risk areas than that achieved by its predecessor while reducing radiation doses to normal structures (Mendenhall et al, 2006). Therefore, IMRT-associated toxicity and locoregional control rates have been promising and have led to lower percentages and severity of radiation-associated complications (Kraaijenga et al, 2015; Lohia et al, 2014; Vergeer et al, 2009; Setton et al, 2012). The past few years have seen the widespread implementation of IMRT as the standard of care for oral and oropharyngeal cancer radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment mainstay in these cases remains radiation therapy alone or in combination with chemotherapy [6, 7]. Since the advent of intensity-modulated radiation therapy (IMRT) in the treatment of head and neck cancer patients, the associated co-morbidities of radiation therapy have been minimized by limiting radiation exposure to healthy tissue and maximizing loco-regional tumor control [810]. Earlier studies looking at the rate of ORN in patients treated in the era of IMRT have reported a reduced prevalence compared to patients treated with conventional radiotherapy [1114].…”
Section: Introductionmentioning
confidence: 99%
“…Une prise en charge par un kinésithérapeute ou un orthophoniste peut être utile, voire un examen de déglutition sous nasofibroscopie ou une radioscopie de déglutition [1]. Si les muscles masticateurs sont inclus dans le faisceau d'irradiation, la mécanothérapie doit être introduite pré-cocement afin de prévenir l'apparition d'un trismus [38][39][40]. Si nécessaire, une réhabilitation prothétique peut améliorer le confort du patient, néanmoins celle-ci doit être atraumatique et réalisée avec prudence sur une muqueuse fragilisée.…”
Section: Réhabilitation Nutritionnelleunclassified